Microbe Profile: Campylobacter jejuni – survival instincts. Issue 3 (31st March 2020) - Gundogdu, Ozan; Wren, Brendan W.
Abstract : Campylobacter jejuni is considered to be the most common bacterial cause of human gastroenteritis worldwide. C. jejuni can cause bloody diarrhoea, fever and abdominal pain in humans along with post-infectious sequelae such as Guillain-Barré syndrome (a paralytic autoimmune complication). C. jejuni infections can be fatal, particularly among young children. C. jejuni are distributed in most warm-blooded animals, and therefore the main route of transmission is generally foodborne, via the consumption and handling of meat products (particularly poultry). C. jejuni is microaerophilic and oxygen-sensitive, although it appears to be omnipresent in the environment, one of the many contradictions of Campylobacter .